Expanding Treatment Opportunities for Hospitalized Patients with Opioid Use Disorders. Issue 1 (18th October 2017) - Winetsky, Daniel; Weinrieb, Robert M.; Perrone, Jeanmarie
Abstract : The prevalence of opioid use disorders (OUDs) is rising across the United States. Patients with OUDs are often hospitalized for medical conditions other than addiction, such as infection, injury, or pregnancy. These hospital admissions provide an opportunity for healthcare providers to initiate opioid agonist therapy with methadone or buprenorphine. Randomized trials have demonstrated the superior effectiveness of this treatment strategy, but its adoption by hospital providers has been slow. A number of barriers have impeded its implementation, including misperceptions about the regulation of opioid prescribing, limited resources for the transition to community‐based treatment, and a lack of familiarity among clinicians about the appropriate initiation and dose adjustment of these opioid agonists for maintenance therapy. We discuss changes in policy and practice to expand opportunities to engage patients with OUDs in opioid agonist treatment during their inpatient hospitalizations.